Immune-mediated diseases are associated with a higher risk of ALS incidence: a prospective cohort study from the UK Biobank - Cao, Wen; Cao, Zhi; Tang, Lu; Xu, Chenjie; Fan, Dongsheng (Frontiers in Immunology, 2024)
Objective: The occurrence of immune-mediated diseases (IMDs) in amyotrophic lateral sclerosis (ALS) patients is widely reported. However, whether IMDs and ALS is a simple coexistence or if there exists causal relationships between the two has been a subject of great interest to researchers.Methods: A total of 454,444 participants from the prospective cohort of UK Biobank were recruited to investigate the longitudinal association between IMDs and ALS. Previously any IMDs and organ specific IMDs were analyzed in relation to the following incident ALS by Cox-proportional hazard models. Subgroup analyses were performed to explore the covariates of these relationships.Results: After adjusting for potential covariates, the multivariate analysis showed that any IMDs were associated with an increased risk of ALS incidence (HR:1.42, 95%CI:1.03-1.94).IMDs of the endocrine-system and the intestinal-system were associated with increased risk of ALS incidence (endocrine-system IMDs: HR:3.01, 95%CI:1.49-6.06; intestinal system IMDs: HR:2.07, 95%CI: 1.14-3.77). Subgroup analyses revealed that immune burden, including IMD duration and the severity of inflammation had specific effects on the IMD-ALS association. In participants with IMD duration≥10 years or CRP≥1.3mg/L or females, previous IMDs increased the risk of incident ALS; however, in participants with IMD duration <10 years or CRP<1.3mg/L or males, IMDs had no effect on incident ALS.Our study provides evidence that previous any IMDs and endocrine-system and the intestinal-system specific IMDs are associated with an increased risk of developing ALS in females, but not in males.